2020
DOI: 10.32859/era.20.45.1-18
|View full text |Cite
|
Sign up to set email alerts
|

A contribution to ethnobotany and review of phytochemistry and biological activities of the Iranian local endemic species Sclerorhachis leptoclada Rech.f.

Abstract: Background: Sclerorhachis leptoclada Rech.f. is endemic to the South Khorassan province in east of Iran. Although S. leptoclada has been widely used as medicinal and edible plant by indigenous people, its ethnobotanical uses have not been well documented yet. This study presents the results of an ethnobotanical survey and reviews phytochemistry and biological activities of S. leptoclada. Methods: The ethnobotanical study was conducted in Birjand and adjacent areas between March 2018 and December 2019. During … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Other ecological factors also play important roles in shaping species' distributions, such as biotic interactions and anthropogenic disturbances (Escobar et al, 2015;Wisz et al, 2013). Particularly, the negative effects of anthropogenic activities, such as irregular harvesting, and development can fragment species' habitats and reduce the distribution of the species in the future (Mohammadi et al, 2021(Mohammadi et al, , 2023.…”
Section: Discussionmentioning
confidence: 99%
“…Other ecological factors also play important roles in shaping species' distributions, such as biotic interactions and anthropogenic disturbances (Escobar et al, 2015;Wisz et al, 2013). Particularly, the negative effects of anthropogenic activities, such as irregular harvesting, and development can fragment species' habitats and reduce the distribution of the species in the future (Mohammadi et al, 2021(Mohammadi et al, , 2023.…”
Section: Discussionmentioning
confidence: 99%
“…Data analysis was carried out using the Relative Frequency (FR) approach which is based on the appearance of information on plant types at the research location. Information species of flowers utilized as number data that has been divided by the total of informants (Kent, 2011;Mohammadi et al, 2020), with the formula as follow:…”
Section: Discussionmentioning
confidence: 99%
“…The province of South Khorassan is one of Iran's major producers and suppliers of medicinal herbs. The use of medicinal herbs is widespread throughout this province and the majority of people still rely on home remedies and traditional medicine for primary healthcare and disease treatment (Mohammadi et al 2020). Birjand, the capital city of South Khorassan province, and its surrounding villages were located in a region historically called "Qohestan" or "Kohistan."…”
Section: Introductionmentioning
confidence: 99%
“…The region is separated from central Iran by Siah-Kuh Mountain range. This geographical isolation has kept the study area relatively pristine so that its inhabitants retain high loyalty to their ancestors' culture and customs (Ivanov 1926, Mohammadi et al 2020. Ahmadi and Eslam (2009) showed that rural people in the region do not consider their quality of life very favorable and it can lead to some social consequences such as increasing migration from villages to cities which gradually would cause changes in lifestyle and the loss of traditional knowledge of these people.…”
Section: Introductionmentioning
confidence: 99%